PERAN MANAJEMEN PENGAWASAN DI PERUSAHAAN KOTA CILEGON DALAM MENINGKATKAN KAPABILITAS KARYAWAN - Putra, Arta Rusidarma; Silfiana, Silfiana (Yayasan Education and Social Center, 2024)
In a company, the existence of quality Supervisory Management is vital to overseeing company operations. This management is a reference for assessing the quality of a company, especially when the majority of ownership is the State. Therefore, good corporate governance is the key to ensuring the company's positive contribution, involving employee morale, planning and ability to respond. This research method uses a qualitative approach and evaluates previous research that is relevant to the topic of discussion. This article reviews